2011
DOI: 10.1371/journal.pone.0016801
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Extended-Spectrum Beta Lactamases among Salmonella enterica Typhimurium Isolates from Pediatric Patients with Diarrhea in China

Abstract: We investigated the extended-spectrum beta lactamases among 62 Salmonella enterica Typhimurium isolates recovered from children with diarrhea in a Chinese pediatric hospital. A large proportion of S. enterica Typhimurium isolates were resistant to multiple antimicrobial agents, including ampicillin (90.3%), tetracycline (80.6%), trimethoprim/sulfamethoxazole (74.2%), chloramphenicol (66.1%), cefotaxime (27.4%). Forty-nine (79.0%) of S. enterica Typhimurium isolates were positive for bla TEM-1b and resistant to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
30
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 24 publications
5
30
0
Order By: Relevance
“…In their report, CTX-M enzymes increased in prevalence from 25% in 2000 to 70% in 2006 among the collected ESBL-producing isolates. CTX-M-55-producing Salmonella isolates have only been reported rarely (18,19). CTX-M-55 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their report, CTX-M enzymes increased in prevalence from 25% in 2000 to 70% in 2006 among the collected ESBL-producing isolates. CTX-M-55-producing Salmonella isolates have only been reported rarely (18,19). CTX-M-55 .…”
Section: Discussionmentioning
confidence: 99%
“…CTX-M-55 is a variant of the CTX-M-15, differing by a single amino acid substitution at position 80 (19,27). Yu et al reported that two isolates harboring CTX-M-55 were highly resistant to cefotaxime and ceftazidime (MICs >256 μg/mL), which was similar to three CTX-M-15-producing isolates having MICs ranging from 32-128 μg/mL for ceftazidime and high resistance to cefotaxime (MIC >256 μg/ mL) (19). These data are consistent with the MICs found for the infectious organism in the present case, which were 16 μg/mL for ceftazidime and >64 μg/mL for cefotaxime.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the extendedspectrum β-lactamase (ESBL) genes cause resistance to third-and fourth-generation cephalosporins in Enterobacteriaceae; TEM and SHV are found frequently in Europe [7], but CTX-M is the most prevalent in Asia [8]. In recent years, Salmonella has been studied extensively worldwide, but relevant studies of the isolation from humans in China were restricted to Shanghai [9], Jiangxi [10,11] and Henan [12] in the south.…”
Section: Introductionmentioning
confidence: 99%
“…The isolate did not harbour bla SHV or bla CTX-M genes and did not express ESBLs as determined by the CLSI-recommended confirmatory double-disk combination test (CLSI, 2008). However, for S. enterica serovar Typhimurium isolates obtained from hospitalized paediatric patients with diarrhoea in the same hospital, broadspectrum cephalosporin resistance was associated with production of CTX-Mtype ESBLs (Yu et al, 2011b).…”
mentioning
confidence: 96%
“…Resistance to fluoroquinolones mainly results from chromosomal alterations in the quinoloneresistance-determining regions (QRDRs) of DNA gyrase (GyrA and GyrB) and topoisomerase IV (ParC and ParE), and from the acquisition of plasmid-mediated quinolone resistance (PMQR) determinants, including QepA efflux, QNR proteins and AAC-(69)-Ib-cr (Cattoir & Nordmann, 2009). Although multidrug resistance to antimicrobials is found commonly among non-typhoidal S. enterica isolates, especially S. enterica serovar Typhimurium isolates (Cui et al, 2009;González-Sanz et al, 2009;Yu et al, 2011b), resistance determinants for S. enterica serovar Thompson isolates are not well-characterized.…”
mentioning
confidence: 99%